Pengaruh Tayangan Program Tonight Show di NET TV terhadap Minat Menonton: Survey pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Jakarta Angkatan 2019 - Ilham Aryasatya; Mulkan Habibi (STIKes Ibnu Sina Ajibarang, 2024)
Television media is an efficient media in reaching a very large number of communicants and relatively far away places. The Tonight Show program is a talk show program that aims to provide information and entertainment to the public. This study aims to measure the influence of the